Challenges in the Prenatal Diagnosis of Cloaca - Lisa B.E. Shields MD; Jeffrey T. White MD, PhD; Dennis S. Peppas MD; Eran Rosenberg MD (Global Pediatric Health, 2020)
Background: Cloaca is a common excretory channel for the genital, urinary, and gastrointestinal tracts. It is considered a severe anorectal malformation caused by failed partitioning of the genital, rectal, and urinary tracts. Methods: We report 5 infants with cloaca at birth who were identified prenatally by one or more of the following on prenatal ultrasound (US): ambiguous genitalia, a cystic pelvic/abdominal mass, hydronephrosis, ascites, a single umbilical artery, and oligohydramnios. Results: A cystic pelvic/abdominal mass and ambiguous genitalia were each observed in 3 cases by prenatal US. Ambiguous genitalia was observed in all 5 neonates at birth. There were 2 twin pregnancies (dichorionic/diamniotic and monochorionic/monoamniotic), with only 1 twin in a set affected with cloaca. Conclusion: Pediatricians should be alert to the prenatal US findings that may raise suspicion of a persistent cloaca to improve both prenatal counseling and family preparation.